2014
DOI: 10.1007/s13730-014-0109-2
|View full text |Cite
|
Sign up to set email alerts
|

Acute severe liver dysfunction induced by febuxostat in a patient undergoing hemodialysis

Abstract: A 58-year-old man with chronic kidney disease (CKD) was admitted to our hospital for hemodialysis (HD) therapy. He had been administered allopurinol (100 mg/ day) before hospitalization, and we replaced it with febuxostat (10 mg/day), a new xanthine oxidase inhibitor. Levels of aspartate aminotransferase, alanine transaminase (ALT), and lactate dehydrogenase were within the normal ranges in the morning before febuxostat administration, but 6 h after administration, these parameters increased markedly to approx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…The biliary system obstruction mechanism is not recognized. The liver volume measured by CT is 1973 cm 3 . b (Day 37): the liver atrophied with massive ascites.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The biliary system obstruction mechanism is not recognized. The liver volume measured by CT is 1973 cm 3 . b (Day 37): the liver atrophied with massive ascites.…”
Section: Discussionmentioning
confidence: 99%
“…b (Day 37): the liver atrophied with massive ascites. The liver volume is 1419 cm 3 . c (Day 284): the liver is regenerating and growing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that benzbromarone could lower the level of blood glucose in db / db mice and inhibit human fatty acid binding protein 4 [ 41 , 46 ]. However, all of them are chemical drugs that can lead to allergies and many side effects [ 47 , 48 ]. They have been demonstrated to produce adverse effects such as hypersensitivity and agranulocytosis [ 49 ].…”
Section: Discussionmentioning
confidence: 99%